The Role of Financial Performance in The Relationship between Ownership on Corporate Value in Environment-Based Companies - Innany Mirrahmatikal Maula; Hersugondo Hersugondo (Postgraduate Program Merdeka University, 2024)
The objective of this research was to examine the impact of Ownership Structure on Corporate value, mediated by Financial performance, among 25 companies listed on the SRI KEHATI Exchange during the period of 2018 to 2022. The data for this study was collected from Bloomberg and official financial reports provided by the Indonesia Stock Exchange (BEI) website. The data analysis in this research was conducted using the Partial Least Squares (PLS) method. The results of the study revealed that the ownership structure, represented by foreign ownership and public ownership, did not exhibit a significant impact on corporate value. Nevertheless, it was noteworthy that foreign ownership demonstrates a statistically significant and positive influence on corporate value by means of the company's financial performance. On the other hand, public ownership exhibited a significant and negative influence on corporate value through the financial performance of the company. This indicated that the financial performance of the company fully mediates the relationship between ownership structure and corporate value. JEL Classification: C51, G32, L25 DOI: https://doi.org/10.26905/afr.v7i3.13124